OPTIMIZATION AND ECONOMIC ANALYSIS OF MULTIPRODUCTS OBTAINED FROM WOOD OF EUCALYPTUS STANDS UNDER DIFFERENT PRODUCTIVE CAPACITY CLASSES AND ROTATION AGES - Viana, Laíssa de Araújo; Castro, Renato Vinícius Oliveira; Souza, Álvaro Nogueira de; Soares, Carlos Pedro Boechat; Joaquim, Maísa Santos; da Costa, Lidiomar Soares (Floresta, 2021)
The present study aimed to analyze the yield and economic viability of the destination, for lumber and energy, of the wood from non-thinned stands of the hybrid Eucalyptus urophylla x Eucalyptus grandis under different productive capacity class and whose production was projected by individual tree growth model to different ages. The simulation of the growth of individual trees was performed by applying the height and diameter growth, and mortality sub-models for three productive capacity classes: high, medium and low. The Kozak model was adjusted to study the stem taper and, in addition, used to optimize patterns for sawing logs and to produce lumber. The economic viability of the projects was evaluated by Net Present Value, Equivalent Periodic Benefit and risk analysis using the Monte Carlo method. It was observed that in areas with less productive capacity the volume of wood destined for energy was greater than 80% and, in areas with greater productive capacity the volume of lumber was greater than 26%. Economic indicators showed that the lumber production was viable at any of the studied rotation age. The risk analysis using the Monte Carlo method did not indicate the possibility of the project being unfeasible under the conditions analyzed. The quantity of different types of products obtained and the wood yield depends on the productive capacity class and age of the stand. The destination of the wood for multiproducts is the most viable option, regardless of the productive capacity class.